Prevalence of insomnia and insomnia symptoms following mild-traumatic brain injury: A systematic review and meta-analysis. (February 2022) - Montgomery, Megan C.; Baylan, Satu; Gardani, Maria
Summary: Sleep is commonly disrupted following mild traumatic brain injury (mTBI), however there is a lack of consensus in the existing literature regarding the prevalence of insomnia/insomnia symptoms after injury. The aim of this review was to conduct a systematic review and meta-analysis of insomnia and insomnia symptoms' prevalence following mTBI. Full-text articles published in English in peer-reviewed journals, including adults with a clinical or self-reported mild traumatic brain injury diagnosis, were eligible for inclusion. Studies that assessed insomnia/insomnia symptoms after injury were included. Of the 2091 records identified, 20 studies were included in the review. 19 of these were meta-analysed (n = 95, 195), indicating high heterogeneity among studies. Subgroup analyses indicated pooled prevalence estimates of post-mTBI insomnia disorder of 27.0% (95% CI 6.49–54.68) and insomnia symptoms of 71.7% (95% CI 60.31–81.85). The prevalence of insomnia is significantly higher in individuals who have sustained mild traumatic brain injury compared to prevalence estimates reported in the general population but high heterogeneity and methodological differences among studies make it difficult to provide reliable prevalence estimates. Future research should continue to advance our understanding of the onset, progression and impact of post-mild traumatic brain injury insomnia to promote the recovery and wellbeing of affected individuals. PROSPERO registration CRD42020168563.